Training delivery methods as source of dynamic capabilities: the case of sports' organisations. Issue 4 (2nd May 2017) - Arraya, Marco António Mexia; Porfírio, Jose António
Abstract : Purpose: Training as an important source of dynamic capabilities (DC) is important to the performance of sports' organisations (SO) both to athletes and to non-athletic staff. There are a variety of training delivery methods (TDMs). The purpose of this study is to determine from a set of six TDMs which one is considered to be the most suitable to enhance performance of SO. Design/methodology/approach: Based on the DC theory, a cross-sectional survey from a sample of 554 workers was used to assess which TDM is considered to be the most efficient and presents higher efficacy, according to the preferences and perception of the staff. Findings: It was concluded that: "on-the-job training" is considered to be the preferred and most effective TDM; formal/informal coaching is the second choice, in terms of perceived effectiveness and "online learning" is considered the least effective TDM. TDM's preferences and results' perceptions do not change according to differentiating issues such as gender, educational level of trainees or even hierarchical position. Research limitations/implications: The present study adopted a cross-sectional survey where relationships and correlations were developed continuously. Although difficult to obtain, it would have been advisable to use a survey based on longitudinal data. Results should only be considered for the purposes of the present sample, although it may be considered that they are generalizable to similar organisations and some preliminary results are raised that worth being analysed further. Practical implications: The outcomes of this study will help managers of SO, according to the situation to be addressed, to choose the best TDM for their non-athletic staff, the ones that will best support their process of continuous improvement and show the best results in terms of renewal of their DC and resources. Originality/value: This study highlights the training process as a source of DC contributing to overall organisation's performance and competitive advantage. It enlarges knowledge on SO, from the pure athletic view to the managerial point of view, and operationalises training to decide the most adequate TDM to improve DC and support the success of SO. Considering that it is usually difficult to measure the concrete results of training on the organisational performance, this is also an important field of study for the management theory in the domain of strategy and human resources because the bridge considered here has not been much developed for a long time.